(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This main objective of this study is to improve the strength of peat soil by adding industrial waste as a filler and cement as a binder. Peat soil are known to have a weak strength and a very high settlement problem. However, past researches have shown that the strength of peat could be improved by using soil stabilization method. In this study, the peat stabilization project includes using bottom ash as the industrial waste which acts as a filler, Portland-limestone cement (PLC) as the binder and the implementation of Bottom Ash as an additive along with the process control agent (PCA) and without process control agent (WPCA). The compressive strength (CS) test are conducted to further study the effect of bottom ash in the strength of stabilized peat. The physical properties of the soil are also studied which includes the density, moisture content, porosity, specific gravity and shrinkage. In order to compare the results, different variation of samples with bottom ash & sand along with PLC are also used to distinguish the roles of different fillers and chemical additive. The comparison will further indicate whether the combination of bottom ash and PLC are suitable for the study of peat stabilization. The proportion for the mix design will be 5 parts of filler (bottom ash/sand), 3 parts of PLC, 5 parts of peat. The samples were casted in the 100 * 100* 100 mm moulds and then were opened after 30 days. The experiments are carried out after the samples have been air cured for 28 days. The compressive strength of the stabilized peat with bottom ash and PLC produces the strength at 3.6 MPa compared to the other samples while as from the previous researches, Peat with sand & PLC having a compressive strength of 0.79MPa. The result shows that the combination of bottom ash as the filler can be used to further improve the strength of peat stabilization.